Two new species of the genus Apolysis (Apolysini, Bombyliidae, Diptera) from the north of Iran - Gharali, Babak; Kamali, Karim; Evenhuis, Neal; Talebi, Ali Asghar (Zootaxa, 2010)
Two new species of the genus Apolysis, A. glabrifrons sp. nov. and A. pusilloides sp. nov. are described from the north of Iran. These species belong to a group of eleven Palaearctic species with a closed discal cell. A key for identifying species of Apolysis in Iran is provided. Species of the genus Apolysis with a closed discal cell in Palaearctic region and the presence of a complex of species within it are briefly discussed.